Structural findings of hysterosalpingography in infertile women in Enugu, southeast Nigeria - Ngozi R Njeze; Salome N Ezeofor (International Journal of Medicine and Health Development, 2020)
Background: In the Nigerian culture, barrenness is a near catastrophe for women. Hysterosalpingography (HSG), being a prime investigation for infertility, is widely used in developing countries because of its positive yield, accessibility, and cost-effectiveness. Aim: The aim of this study was to identify the pattern and the most common radiologic findings in the HSG of women with infertility in Enugu, southeast Nigeria. Materials and Methods: This was a cross-sectional study involving 160 female patients who presented at the gynecology clinic of a private hospital in Enugu, Nigeria with clinical impression of infertility. The women were in turn referred to the radiology center for HSG. Data were analyzed using RStudio. Results: A total of 254 radiologic features were obtained as some patients had more than one radiological findings. The age range of the participants was 20 - 46 years, and the most prevalent age group was 25 - 29 years (31.1%). The most common clinical type of infertility was secondary infertility.The most common abnormal cervical and uterine findings were synechia (80%) and fibroids (65%) respectively. Bilateral tubal blockage 29.4% was the most common finding in the fallopian tubes. Normal findings were seen in 5.44%. Conclusion: Synechia and fibroids were the most common abnormal radiologic findings in the cervix and uterus, respectively. HSG was found to be informative in infertility evaluation, hence should still be recommended as a first-line imaging modality in infertility.